A Regularly Structured Parallel Multiplier with Low-power Non-binary-logic Counter Circuits. Issue 3 (2001) - Lin, Rong
Abstract : A highly regular parallel multiplier architecture along with the novel low-power, high-performance CMOS implementation circuits is presented. The superiority is achieved through utilizing a unique scheme for recursive decomposition of partial product matrices and a recently proposed non-binary arithmetic logic as well as the complementary shift switch logic circuits. The proposed 64×64-b parallel multiplier possesses the following distinct features: (1) generating 64 8×8-b partial product matrices instead of a single large one; (2) comprising only four stages of bit reductions: first, by 8×8-b small parallel multipliers, then, by small parallel counters in each of the remaining three stages. A family of shift switch parallel counters, including non-binary (6, 3) ∗ and complementary (k, 2) for 2 ≤ k ≤ 8, are proposed for the efficient bit reductions; (3) using a simple final adder. The non-binary logic operates 4-bit state signals (representing integers ranging from (0 to 3), where no more than half of the signal bits are subject to value-change at any logic stage. This and others including minimum transistor counts, fewer inverters, and low-leakage logic structure, significantly reduce circuit power dissipation.